GOVERNMENT INVESTITURE - Elena Emilia ȘTEFAN (Challenges of the Knowledge Society)
This study aims to analyze the procedure of the investiture of the Government and to briefly present current configuration of the Romanian Government. In this respect, based on the current legislation and on the analysis of the public activity official information, ministries which currently operate according to government program, as well as the modality the government program is established or the list of the future members of the cabinet is drawn up will be summarized. We believe that this is a highly topical issue, the Government being the public authority which, according to the provisions of the Constitution ensures the performance of domestic and external policy of the country and it is important to know the structure of the Government, especially since our country is quite familiar with the government investiture procedure since recent Governments had a rather short term of office. The area covered by the subject we propose is quite extensive and includes a combination between constitutional law, parliamentary law, administrative law and general theory of law. The following are among the scopes of this study: the performance of an inventory of the ministries that make up the current Government; brief presentation of the Government investiture procedure and of the meaning of the government political program, due to the fact it is an extremely up-to-date subject and we strongly believe that it is important to understand the constitutional mechanism of making up the Government.